Social theories from Latin America - Olano Alor, Aldo (2019)
It is proposed to highlight the coloniality of knowledge within the social sciences in Latin America and appeals to theories immersed in the debate organized around the new paradigm, postwesternism. To understand the regional expansion of this coloniality, the first section resorted to a transdisciplinary methodology on the formation of a knowledge for the studies of the society, the scientific-rational, in particular the global positioning of the Cartesian method as the foundation of scientific knowledge; the second, revises the institutionalization of the social sciences and the Assigned Mission: Foundation of faculties and departments in the universities of the region, grouping the disciplines and professionals in charge of studying the society in its components. These were the mechanisms to preserve the coloniality ofknowledge in relevant academic and intellectual circles of the continent.